2006
DOI: 10.1161/01.atv.0000194155.96456.b7
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Growth Are Attenuated in Vascular Smooth Muscle Cells With Type VIII Collagen-Null Alleles

Abstract: Objective-Type VIII collagen is upregulated after vascular injury and in atherosclerosis. However, the role of type VIII collagen endogenously expressed by smooth muscle cells (SMCs) and in the context of the vascular matrix microenvironment, which is rich in type I collagen, is not known. To address this, we have compared aortic SMCs from wild-type (WT) mice to SMCs from type VIII collagen-deficient (KO) mice when plated on type I collagen. Methods and Results-Type VIII collagen was upregulated after wounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…That specific collagen type, which is upregulated in response to vascular injury, 37 has a role opposite to that of collagen type 1 in that it promotes vascular smooth muscle cell migration. 38 The upregulation of this transcript, together with the downregulation of other isoforms in aging males, again supports the notion that this group is more susceptible to neointimal proliferation, vascular smooth muscle cell migration, and potentially atherosclerosis. The second major difference was in elastin density, which decreased selectively in old males.…”
Section: Discussionsupporting
confidence: 54%
“…That specific collagen type, which is upregulated in response to vascular injury, 37 has a role opposite to that of collagen type 1 in that it promotes vascular smooth muscle cell migration. 38 The upregulation of this transcript, together with the downregulation of other isoforms in aging males, again supports the notion that this group is more susceptible to neointimal proliferation, vascular smooth muscle cell migration, and potentially atherosclerosis. The second major difference was in elastin density, which decreased selectively in old males.…”
Section: Discussionsupporting
confidence: 54%
“…Collagen VIII has previously been shown to facilitate migration of smooth muscle cells. 230,232,233 Consistently, the migratory capacity was markedly reduced in collagen VIII KO cardiac fibroblast. Thus, collagen VIII appeared to mediate not only differentiation of fibroblasts into myofibroblasts, but also important aspects of myofibroblast function.…”
Section: The Multiple Roles Of Syndecan-4 In Cardiac Remodelingmentioning
confidence: 56%
“…Collagen VIII can direct adherence to ECM molecules, such as the structural collagen I, 230 and is suggested to serve as a molecular bridge between different ECM molecules. 136 In…”
Section: The Multiple Roles Of Syndecan-4 In Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in glomerular capillary length that leads to glomerular hypertrophy has been observed in mice with diabetic nephropathy (Guo et al, 2005). It has been reported that vascular smooth muscle cells expressing type VIII collagen can modify the microenvironment and can spread and migrate on the tissue without type I collagen (Adiguzel et al, 2006). There is no report of the downregulation of type I collagen during the formation of fibrosis; therefore, the meaning of the downregulation of Col1a1 remains unclear.…”
Section: Discussionmentioning
confidence: 99%